Neighborhood Unit and Neighboring - Reza Serali; Shahram Pourdeihimi (صفه)
‘Neighborhood’ is a term frequently used in environmental design for referring to diverse interrelated concepts. The ambiguity in exact definition of this term has often led to confusion in both theory and practice, however. This paper tries to clarify possible usages of this term, as well as its implications and nuances to develop a conceptual framework for studies of mutual interactions between neighboring residents in a community. Two common connotations for the term ‘neighborhood’ are recognized to be the ‘neighborhood unit’ and the actual act of ‘neighboring’. Although both these concepts have ‘physical’, ‘social’ and ‘cognitive’ dimensions, there are major disparities between them that makes them fundamentally different. While, the ‘neighborhood unit’ is essentially a physical entity for promoting social interactions between the residents over a certain area, ‘neighboring’ denotes such interactions at different scales and in diverse physical surroundings.